Tsunamis along the Azores Gibraltar plate boundary - Baptista, Maria Ana Carvalho Viana (2020)
The Eurasia-Nubia plate boundary between the Azores and the Strait of Gibraltar has been the place of large tsunamigenic earthquakes. The tectonic regime is extensional in the Azores, transcurrent along the Gloria Fault, and compressional in the Strait of Gibraltar. Here, the plate boundary is not clearly defined. The knowledge of past events that occurred in the area constitutes an essential contribution to the evaluations of seismic and tsunami hazard in the North-East Atlantic. In this study, we present an overview of the six major events in the area and show the use of tsunami data to add some constraints on their source. The historical events occurred in the eighteenth-century between 1722 and 1761, while the twentieth-century events occurred between 1941 and 1975. We speculate that major tsunamigenic earthquakes that occur in the Iberia-Maghreb area take place at the boundaries of a lithospheric block approximately defined by the location the six events summarized here, which role and dynamics are not yet understood.